The Effect of Taxation on Economic Development of India - Pande, Navodita (Digital Repository of Theses, 2024)
India is a mixed economy since independence from the British. She, under the leadership of prime minister Jawaharlal Nehru, underwent a phase of expansion, expanding on the agricultural sector, manufacturing sector and the services sector. As years proceeded, Indian economy continued to remain mixed, being governed by the market forces under the capitalist structures and functioning in accordance with the socialist forces through government welfare schemes and public expenditure by various governments across different sectors. The study assesses these policies to devise a framework for existing good policies that facilitate economic development of India. The methods used for this study are semistructured interviews of fifteen tax officials and lawyers who have sufficient knowledge of how taxation impacts the development of a country. There was an alternate hypothesis which was proven correct by the findings and results. In order to keep the study relevant, content analysis of the budget speech by finance minister Nirmala Sitharaman was conducted with different coding themes. These themes are studied, and the results are discussed below. Fifteen respondents had diverse opinions on how direct and indirect tax impacts development. Ten respondents believed that India is on the right growth trajectory with government policies that encourage discrete expenditure of public revenue for developmental purposes. Twelve respondents said that infrastructure should be the focus while allocating funds and resources for developmental tasks besides social alleviation of the marginalized in India. Content analysis results indicated the frequency of the words ‘taxation’ and ‘development’ in the budget speech by finance minister of India in July 2024. The words ‘taxation’ and ‘development’ were analysed as themes in the report with resultant discussions on taxation, public expenditure and economic development. Correlations were formed and results were linked to the literature review analysed under different themes. Thematic discussion led to different ideas about how tax-spend by governments impacts expenditure in the public domain and benefits citizens.